Top incomes in South Africa in the twentieth century - Gonzalez Alvaredo, Facundo (2022)
There have been important studies of recent income inequality and of poverty in South Africa, but very little is known about the long-run trends over time. There is speculation about the extent of inequality when the Union of South Africa was formed in 1910, but no hard evidence. In this paper, we provide evidence that is partial—being confined to top incomes—but which for the first time shows how the income distribution changed on a (near) annual basis from 1913 onwards. We present estimates of the shares in total income of groups such as the top 1% and the top 0.1%, covering the period from colonial times to the twenty-first century. For a number of years during the apartheid period, we have data classified by race. The estimates for recent years bear out the picture of South Africa as a highly unequal country, but allow this to be placed in historical and international context. The time series presented here will, we hope, provide the basis for detailed investigation of the impact of South African institutions and policies, past and present. But the similarity of the changes over time in top incomes across the four ex-dominions suggests that national developments have to be seen in the light of common global forces.